Efektifitas Penggunaan Pasar Rakyat Desa Bonto Tengnga di Kecamatan Sinjai Borong - Muhammad Amar; Makmur Makmur; Fajaruddin Fajaruddin; Suzi Alfitra (Lembaga Pengembangan Kinerja Dosen, 2024)
The type of research in this study is a qualitative research method with description format, while the data collection techniques in this study are: observation, interviews, documentation. Then the data analysis techniques used is data collection, data reduction and conclusion drawing. Informants namely: Department of Industry and Trade of Sinjai Regency, Secretary of Bonto Tengnga Village, Market Traders of Sinjai Village. Tengnga, Bonto Tengnga Village Market Traders, buyers, Bonto Tengnga Village Community. Tengnga Village Community. The results of research on the Effectiveness of the Use of the Village People's Market Bonto Tengnga in Sinjai Borong sub-district, in terms of the number of traders and stalls concluded that the number of traders selling is around 10 people while the available kiosks are 12 but only one kiosk is used. there are 12 but only one kiosk is used. In terms of buyer interest in the People's Market Bonto Tengnga People's Market is still lacking buyers due to the market schedule which is close to the markets in Sorong. with the markets in Sinjai Borong, as well as the lack of income of the surrounding community, most of whom work as shopkeepers. surrounding communities who mostly work as farmers. In terms of Constraints and Obstacles to the Management of the People's Market, the regulation of traders in buying and selling in the market because sometimes the fields do not follow the rules of the market. in the market because sometimes the fields do not follow the government regulations that have been determined and the traders prefer to follow the regulations. government regulations that have been determined and traders prefer to sell in front of the market because they assume that buyers are buyers. because they think that buyers are always in front and do not keep the market clean. market cleanliness.